Vitamin D levels in children with severe hemophilia A. Issue 3 (April 2015) - Albayrak, Canan; Albayrak, Davut
<x xml:space="preserve">Abstract</x> Osteoporosis in hemophilic patients is a significant problem. The causes of osteoporosis in hemophilic patients are lack of adequate exercise, multiple hemorrhage and inflammation, and low vitamin D levels. The aim of this study was to retrospectively determine the frequency of vitamin D deficiency and insufficiency in children with severe hemophilia A. Forty-seven children with severe hemophilia were included in the study. None of the patients had previously received vitamin D supplementation. No patient had clinical or radiologic findings of rickets or seropositivity of hepatitis C virus or HIV. The mean age of the patients was 11.64 ± 5.70 (range, 2–18) years. The mean vitamin D level was 16.35 ± 7.49 ng/ml (range, 3.25–33.80). Vitamin D levels were below 10 ng/ml (severe vitamin D deficiency) in 9 cases (19%), between 10 and 19.99 ng/ml (vitamin D deficiency) in 23 cases (49%), between 20 and 29.99 ng/ml (vitamin D insufficiency) in 13 cases (28%), and above 30 ng/ml (normal vitamin D level) in 2 cases (4%). The mean serum levels of 25-hydroxy vitamin D in the children with hemophilia during winter and autumn were significantly lower than that during summer (P = 0.0028 and P = 0.0091, respectively). A majority of our hemophilic patients (96%) had low vitamin D levels. The study showed that the risk of vitamin D deficiency is the most highest during winter and autumn. Normal lifelong vitamin D levels are especially important in hemophilia because of the possible synergistic effect of vitamin D levels on periarticular and general osteoporosis, which is intrinsic to hemophilic conditions. We advise routine checking of vitamin D levels twice a year and vitamin D supplementation to maintain its level between 30 and 100 ng/ml.